Efficacy of probiotics/synbiotics supplementation in patients with chronic kidney disease: a systematic review and meta-analysis of randomized controlled trials - Liu, Chang; Yang, Letian; Wei, Wei; Fu, Ping (Frontiers in Nutrition, 2024)
Background Chronic kidney disease (CKD) is a serious and steadily growing health problem worldwide. Probiotic and synbiotic supplementation are expected to improve kidney function in CKD patients by altering imbalanced intestinal flora, regulating microbiota metabolites, modulating the brain-gut axis, and reducing inflammation. Objectives Our aim is to report the latest and largest pooled analyses and evidence updates to explore whether probiotic and synbiotic have beneficial effects on renal function and general conditions in patients with CKD. Methods We conducted a systematic literature search using PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials from inception until 1 December 2023. Eligible literatures were screened according to inclusion and exclusion criteria, data were extracted, and a systematic review and meta-analysis was performed. Measurements included renal function-related markers, inflammatory markers, uremic toxins, lipid metabolism-related markers and electrolytes levels. Results Twenty-one studies were included. The results showed that probiotic/synbiotic significantly reduced blood urea nitrogen (BUN) (standardized mean difference (SMD), −0.23, 95% confidence interval (CI) −0.41, −0.04; p = 0.02, I2 = 10%) and lowered c-reactive protein level (CRP) (SMD: −0.34; 95% CI: −0.62, −0.07; p = 0.01, I2 = 37%) in CKD patients, compared with the control group. Conclusion In summary, probiotic/synbiotic supplementation seems to be effective in improving renal function indices and inflammation indices in CKD patients. Subgroup analyses suggested that longer-term supplementation is more favorable for CKD patients, but there is a high degree of heterogeneity in the results of partial subgroup analyses. The efficacy of probiotic/synbiotic in treating CKD needs to be supported by more evidence from large-scale clinical studies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024526836, Unique identifier: CRD42024526836.